PEMANFAATAN NEW MEDIA UNTUK EFEKTIVITAS KOMUNIKASI DI ERA PANDEMI - fikri shofin mubarok (Program Studi Ilmu Komunikasi FBIK Unissula, 2022)
The Covid-19 pandemic that hit the world at the end of 2019 brought a torrent of changes in human life. The starting point for change occurs mainly in the aspect of human communication. The Covid-19 virus is transmitted through droplets in human activities. Where as an effort to contain the pandemic, face-to-face meetings are avoided. So direct communication that causes crowds in various public places is avoided and prohibited so as not to become a base for virus transmission. As a result, communication switches to new media through a set of digital technologies that are connected to the internet. Along with the advancement of the digital era in the 21st century, the role of new media as a means of communication is very urgent. This research is in the form of descriptive qualitative describing that the role of new media in the pandemic era is able to create effectiveness in supporting the continuity of social-community life.